2019
DOI: 10.1002/cctc.201801843
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Catalytic Production of Platform Chemicals from Holocellulosic Biomass

Abstract: This Review discusses novel catalytic pathways of lignocellulosic biomass to value‐added chemicals including biomass‐derived sugar alcohols, organic acids, furans and biohydrocarbons. These production approaches are undertaken by biological, chemical and thermochemical transformations or a combination of them. Nevertheless, the majority of research in this area is focused on the design of heterogeneous catalysts to convert value‐added products from holocellulosic biomass. Biorefineries represent the peak of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(47 citation statements)
references
References 247 publications
(348 reference statements)
3
44
0
Order By: Relevance
“…This ongoing trend can give a new potential to existing forest companies to also develop as significant bio-based chemical and biofuel producers, in addition to cellulose-based products. This position urges to transform their mass production of paper-grade pulp en route to other products with smaller production quantity but larger gross margin, such as methane gas from wastewater [4]; bio-oil from lignin [5]; and value-added chemicals like furfural (FUR), hydroxymethylfurfural (HMF), and acetic acid from hydrolysate liquor from dissolving pulp [6]. An attractive sugar contained in high amounts, xylose, has not yet been fully utilized in the paper and pulp industry, which is mixed with lignin-derived compounds and burned to provide process heat [7].…”
Section: Introductionmentioning
confidence: 99%
“…This ongoing trend can give a new potential to existing forest companies to also develop as significant bio-based chemical and biofuel producers, in addition to cellulose-based products. This position urges to transform their mass production of paper-grade pulp en route to other products with smaller production quantity but larger gross margin, such as methane gas from wastewater [4]; bio-oil from lignin [5]; and value-added chemicals like furfural (FUR), hydroxymethylfurfural (HMF), and acetic acid from hydrolysate liquor from dissolving pulp [6]. An attractive sugar contained in high amounts, xylose, has not yet been fully utilized in the paper and pulp industry, which is mixed with lignin-derived compounds and burned to provide process heat [7].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review has reported advances in the catalytic production of attractive molecules from lignocellulosic biomass, which includes promising furanic compounds [5]. Moreover, readers may encounter other interesting reviews that cover the field of FUR-upgrading in a broader perspective [55,56].…”
Section: Scope Of the Reviewmentioning
confidence: 99%
“…This current tendency can bring new markets to current forest firms to further expand their product portfolios with biobased chemicals and biofuels, as an extension to their cellulose-based products, such as paper and packaging materials. This situation forces the shift of their bulk production of paper-grade pulp on the way to other products with lower production volumes but higher profit, such as bio-oil from lignin [3], and value-added chemicals like xylitol [4], furfural (FUR), 5-hydroxymethylfurfural (HMF) and acetic acid from hydrolysate liquor from the dissolving pulp production [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…FA is also a biomass product obtained from lignocellulose; both FA and LVA are produced in equal proportions from hemicellulose acid catalysis [1b,6] . FA is an ideal hydrogen donor in LVA reduction.…”
Section: Introductionmentioning
confidence: 99%